THE INFLUENCE OF CAPITAL ADEQUACY RATIO, NON-PERFORMING FINANCING, FINANCING TO DEPOSIT RATIO AND OPERATING EXPENSES TO OPERATING INCOME ON PROFITABILITY OF ISLAMIC BANKING IN INDONESIA - Siti Hardiyanti Marpaung; Erlina; Chandra Situmeang (CV. Radja Publika, 2025)
This study aims to analyze and determine the effect of Capital Adequacy Ratio (CAR), Non Performing Financing (NPF) Operating Costs to Operating Income (BOPO), on Profitability with Return on Assets (ROA) of Islamic Commercial Banks in Indonesia from 2016 to 2023. In addition, this study also aims to determine whether there are differences between the values of CAR, NPF, FDR, BOPO and ROA at Islamic Commercial Banks in the period before and after the COVID-19 pandemic. So that in this study, the research period is divided into the period before (2016-2019) and after (2020-2023) the COVID-19 pandemic. The type of research conducted is quantitative research. The samples in this study were 9 Islamic Commercial Banks in Indonesia so that the total observations in this study amounted to 72 data. The data obtained was then analyzed using SPSS. The analysis method used is Multiple Linear Regression Analysis and Paired Sample t-Test for hypothesis testing. Based on the results of data processing using hypothesis testing, it shows that partially CAR has a positive and significant effect on ROA, NPF has a negative and significant effect on ROA, FDR has no effect on ROA, and BOPO is also proven to have no effect on ROA at Islamic Commercial Banks. The results of the t-test explain that there are significant differences in the values of CAR, NPF and ROA in the period before and after the COVID-19 pandemic, while FDR and BOPO did not experience significant changes in the period before and after the COVID-19 pandemic in Islamic Commercial Banks.